2015
DOI: 10.1080/19349637.2014.957609
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Beliefs and Practices, Religiosity, and Spiritual Well-Being Among Jordanian Arab Muslim University Students in Jordan

Abstract: This study explores the associations between spiritual beliefs and practices, religiosity, and spiritual well-being for Jordanian Arab Muslim university students. A convenience sample of 553 students was recruited from northern Jordan. The findings showed that participants with greater spiritual beliefs and practices and religiosity were more likely to have better spiritual well-being, religious well-being, and existential well-being. Only income had a significant effect on the spiritual well-being and existen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…Both scales were converted to Z scores by gender before being used in the analysis. Evidence of reliability and convergent-related validity for this scale has been reported in previous studies (Musa, 2015;Musa & Pevalin, 2011;Musa & Pevalin, 2015). In this study the internal consistency of the religiosity scale for females and males were acceptable to high with alpha coefficients of 0.77 and 0.82, respectively.…”
Section: Religiositymentioning
confidence: 87%
“…Both scales were converted to Z scores by gender before being used in the analysis. Evidence of reliability and convergent-related validity for this scale has been reported in previous studies (Musa, 2015;Musa & Pevalin, 2011;Musa & Pevalin, 2015). In this study the internal consistency of the religiosity scale for females and males were acceptable to high with alpha coefficients of 0.77 and 0.82, respectively.…”
Section: Religiositymentioning
confidence: 87%
“…Spiritual well-being among university students was investigated in various studies, Musa (2015) showed that university students reported relatively high means of spiritual well-being among both males and females. Moreover, spiritual well-being was associated with better college adjustment (Kneipp, Kelly, & Cyphers, 2009), stronger engagement in health-promoting behaviors (Hsiao, Chien, Wu, Chiang, & Huang, 2010), better quality of life and higher levels of happiness (Abdel-Khalek, 2010), and higher levels of social support (Taliaferro, Rienzo, Pigg, Miller, & Dodd, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, praying, reading Quran, doing zakat, and doing hajj enhance the vertical dimension of spiritual wellbeing (relationship between self and god) (Musa & Pevalin, 2012;Moberg, 2002). Therefore, the findings suggest that Muslims and Arab youth may use spiritual well-being and its dimensions (meaning/ peace, and faith) as a coping mechanism to achieve a state of peace, comfort, and psychological well-being (Musa, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In Islam religion, (which is the religion that followed by the majority of students) amnesty, forgiveness and remission to others are important values that decrease aggression and promote positive social interactions. Lastly, aggression is considered unethical and contradictory with the teachings of Islamic and Christian religions (Musa, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation